Frog - Luscombe, Abi; Grimes, Amy (London dorling kindersley limited, 2024)
A colourful pop-up board book that introduces little ones to the exciting life cycle of a frog. Wander down to the water and discover how a tiny tadpole transforms into a lively, hopping frog
Scientific notions
Keywords: Board books; Frogs Life cycles Pictorial works -- Juvenile literature; Picture books